2008
DOI: 10.3748/wjg.14.5436
|View full text |Cite
|
Sign up to set email alerts
|

Direct hemoperfusion with a polymyxin B-immobilized cartridge in intestinal warm ischemia reperfusion

Abstract: AIM:To investigate the effectiveness of direct hemoperfusion with polymyxin B-immobilized fibers (DHP-PMX therapy) on warm ischemia-reperfusion (I/R) injury of the small intestine. METHODS:The proximal jejunum and distal ileum of mongrel dogs were resected. Warm ischemia was performed by clamping the superior mesenteric artery (SMA) and vein (SMV) for 2 h. Blood flow to the proximal small intestine was restored 1 h after reperfusion, and the distal small intestine was used as a stoma. The experiment was discon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Although there is no clinical evidence regarding the effect of PMX-DHP on reperfusion injury, there is an experimental study demonstrating that PMX-DHP signifi cantly reduced mesenteric reperfusion injury. 9 Endotoxin adsorption is a safe treatment with few adverse effects, as a pilot study demonstrated, 10 and incorporating it into the CPB is technically simple and easy. 7…”
Section: Discussionmentioning
confidence: 98%
“…Although there is no clinical evidence regarding the effect of PMX-DHP on reperfusion injury, there is an experimental study demonstrating that PMX-DHP signifi cantly reduced mesenteric reperfusion injury. 9 Endotoxin adsorption is a safe treatment with few adverse effects, as a pilot study demonstrated, 10 and incorporating it into the CPB is technically simple and easy. 7…”
Section: Discussionmentioning
confidence: 98%
“…Especially in situations of small intestinal transplantation, IR of the graft is an inevitable consequence of the surgical process, and the reduction of IR injury to the graft is a crucial factor in determining the success of small intestinal transplantation. We have already reported some studies on reducing IR injury of the small intestine [3][4][5][6]; however, those reports were still not sufficient to inhibit IR injury completely.…”
Section: Introductionmentioning
confidence: 99%
“…Polymyxin B (PMX) is an antibiotic, which binds to LPS of GNB and inactivates the endotoxin with increased affinity. Hemofiltration with PMX hemoperfusion (PMX-HP, Toraymyxin, Toray Industries, Tokyo, Japan) immobilized to a polysterene-derived fiber was developed in Japan in the 1990s, to selectively adsor and remove the endotoxin of GNB in the blood stream[5,7-9]. Since 2017, our institution have used the PMX-HP in selected patients who underwent surgery for the treatment of septic shock originated from abdominal peritonitis.…”
Section: Introductionmentioning
confidence: 99%